Balance sheet and list of subscriptions to the Connolly Tour Committee by William O'Brien for the Socialist Party of Ireland to fund James Connolly's lecture tour of Ireland and Great Britain - O'Brien, William, 1881-1968 (1910)
Includes balance sheet of income and expenditure and a list of subscribers and the amount of their donations. See MS 13,919/1 for notebook of subscriptions.
Keywords: Connolly, James, -- 1868-1916; Socialist Party of Ireland; Connolly Tour Committee; Ireland -- Politics and government -- 1901-1910